Mens rea of Murder in the Islamic Penal Code (2012) - Hasan Moradi; Ali Shahbazi (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2015)
One of the main constituents of murder is mens rea or mental element. Actually, the difference of murder and involuntary manslaughter is mens rea which has different components including general ill will (intention of behavior or the purpose of action) and particular ill will (intention of the result or purpose of the result). The current paper, in addition to explaining mens rea of murder, analyzes the knowledge and volition as the first and the most important components of mens rea and also the status and role these two components. This paper concludes that although the Islamic Penal Code (2012) comparing with former codes has innovation, has still some failures. Hence, there are some issues which shall be rethought about them including: murder by omission, attention to leaving an action in murdering, affirmation of the action purpose done on victim as the authentication of intention in crime, voluntarily behavior in murder and also making difference between first degree murder (premeditated killing) and second degree murder (non-premeditated killing).